Anatomi leher dan kondisi patologisnya: Pemeriksaan USG - Lusi Epsilawati; Azhari Azhari; Norlaila Sarifah (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2020)
Objectives: This study is aimed to introduce an overview of the anatomy of the neck region as well as an overview of some pathological conditions that can be seen through Ultrasound. Literature Review: There was a characteristic in the anatomy of the neck by Ultrasound. Anatomy of the neck on Ultrasound, divided into several areas with its characteristics. Ultrasound can thoroughly assess pathological conditions related to anatomy. Conclusion: Ultrasound was a modality that can be used to see the condition of the anatomy, including the neck area. Pathological conditions were also able to be appropriately seen through Ultrasound.